Factors Affecting Rural Households' Charcoal and Firewood Production in Selected Dryland Woredas of Oromia and Afar regions - Girma, Gonche; Abate, Tensaye; Yohannes, Temesgen; Belachew, Azmera (LPPM of NAROTAMA UNIVERSITY, 2025)
This study set out to investigate the variables that influence households' participation in the production of woodfuel in the dryland regions of Ethiopia's Oromia and Afar regions. Using snowball sampling, 231 households in total were sampled. Out of the 231 sample houses, 155 of them produced wood fuel, and the remaining 76 did not. Focus groups and surveys of households were used to gather data. A binary probit regression model and descriptive statistics were used to analyze the data. The findings showed that households producing wood fuel do so because it is their primary source of income during times of household food scarcity, lack of other work options, and occurrence of various shocks including drought and other diseases affecting crops and livestock. The majority of the labor used in the household to produce woodfuel came from family members. Results from the binary probit model demonstrated that access to extensions and education, both of which were shown to be statistically significant, have a negative impact on household participation in the production of woodfuel. Conversely, the ownership of animals, income, the frequency of droughts, and livestock diseases all had a beneficial impact on household participation in the production of woodfuel. Because there are many different methods of producing wood fuel, policymakers must consider the best approaches to promoting the sustainable use of dryland forest management as well as socioeconomic intervention alternatives that support alternative lifestyles.